COLUMNAR-CELLED METAPLASIA AND ADENOCARCINOMA OF THE ESOPHAGUS IN INHABITANTS OF THE LENINGRAD OBLAST (BY THE DATA OF ESOPHAGOGASTRODUODENOSCOPY) - D. I. Vasilevsky; D. S. Silantiev; K. V. Mikhaleva; A. S. Pryadko; A. V. Filin; S. L. Vorobiev; S. N. Mednikov; A. V. Luft; V. I. Kulagin; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова)
The article presents an analysis of results of 24 384 endoscopic examinations of the upper gastrointestinal tract in population of the Leningrad oblast with symptoms of gastric dyspepsia during the period from 2007 to 2011. The detection of the columnar-celled metaplasia was 1.1%, adenocarcinoma of the esophagus — 0.045%. Esophageal adenocarcinoma occurred in 3.95% of cases of the column-celled esophagus. Barrett’s esophagus was revealed in males more often than in women (56.5% and 54.5% respectively). The peak incidence of esophageal adenocarcinoma in males was at the age from 46 to 60 years (36.4% of patients), in females — from 61 to 75 years (27.3% of patients). Intestinal metaplasia was detected in 72.7% of cases with esophageal adenocarcinoma. The diagnosis of long and short segment of column-celled esophagus revealed no significant difference in the development of esophageal adenocarcinoma.